Photoisomerization mechanism of the rhodopsin chromophore: picosecond photolysis of pigment containing 11-cis-locked eight-membered ring retinal. - Mizukami, T (1993)
The primary photochemical event in rhodopsin is an 11-cis to 11-trans photoisomerization of its retinylidene chromophore to form the primary intermediate photorhodopsin. Earlier picosecond studies have shown that no intermediate is formed when the retinal 11-ene is fixed through a bridging five-membered ring, whereas a photorhodopsin-like intermediate is formed when it is fixed through a flexible seven-membered ring. Results from a rhodopsin analog formed from a retinal with locked 11-ene structure through the more flexible eight-membered ring (Ret8) are described. Incubation of bovine opsin with Ret8 formed two pigments absorbing at 425 nm (P425) and 500 nm (P500). P425, however, is an artifact because it formed from thermally denatured opsin or other proteins and Ret8. Excitation of P500 with a picosecond green pulse led to formation of two intermediates corresponding to photo- and bathorhodopsins. These results demonstrate that an appearance of early intermediates is dependent on the flexibility of the 11-ene and that the photoisomerization of P500 proceeds by stepwise changes of chromophore-protein interaction, which in turn leads to a relaxation of the highly twisted all-trans-retinylidene chromophore in photorhodopsin.